2021
DOI: 10.26434/chemrxiv.14186561.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling the Proteome-Wide Selectivity of Diverse Electrophiles

Abstract: <p><a>Targeted covalent inhibitors are powerful entities in drug discovery, but their application has so far mainly been limited to addressing cysteine residues. The development of cysteine-directed covalent inhibitors has largely profited from determining their proteome-wide selectivity using competitive residue-specific proteomics. Several probes have recently been described to monitor other amino acids using this technology and many more electrophiles exist to modify proteins. Nevertheless, a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Critical to the success of the SP3-Rox method was our application of the FragPipe computational pipeline for highly sensitive peptide identification, as well as rigorous vetting of the FragPipe's built-in quantification module IonQuant by comparison with Skyline quantification. While proteomics tools such as FragPipe and Skyline have been widely adopted by the proteomics community, their use in chemoproteomics and redox proteomics has been limited to a handful of examples ( 40 , 88 , 89 ). Building upon our prior findings that MSFragger is compatible with search of chemoproteomics data generated using a FAIMS device for online fractionation, we first confirmed that search of samples labeled with the heavy and light IAA probes at a 1:1 stoichiometry afforded comparable PSMs for light- and heavy-labeled peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Critical to the success of the SP3-Rox method was our application of the FragPipe computational pipeline for highly sensitive peptide identification, as well as rigorous vetting of the FragPipe's built-in quantification module IonQuant by comparison with Skyline quantification. While proteomics tools such as FragPipe and Skyline have been widely adopted by the proteomics community, their use in chemoproteomics and redox proteomics has been limited to a handful of examples ( 40 , 88 , 89 ). Building upon our prior findings that MSFragger is compatible with search of chemoproteomics data generated using a FAIMS device for online fractionation, we first confirmed that search of samples labeled with the heavy and light IAA probes at a 1:1 stoichiometry afforded comparable PSMs for light- and heavy-labeled peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, sulfonyl fluoride-based probes are not completely selective for lysine and have also been used to target tyrosine residues 209 . A recent preprint reported the use of a chemoproteomic approach to profile the amino acid reactivity preference of 54 different electrophiles, which will prove to be a great resource for covalent ligand discovery 210 . Combining comprehensive electrophile profiling, lysine-directed chemoproteomics and structure-guided approaches will enable scientists to leverage the abundance of lysine residues adjacent to ligand binding sites to enhance covalent drug discovery.…”
Section: The Covalent Drug Discovery Toolboxmentioning
confidence: 99%
“…3A) (40). In an unbiased analysis (41), we detected modified peptides with the added mass of the adduct with PE-P plus light or heavy isoDTB tag, respectively (Fig. 3B).…”
Section: Insights Into the Mechanism Of Pe-p Bindingmentioning
confidence: 97%
“…Analysis of the modifications introduced by PE-P proteome-wide. (A) Workflow applied to study binding mode and sites of PE-P using isotopically labeled desthiobiotin (isoDTB) tags(39,41). V. campbellii lysate was treated with 10 µM PE-P (blue circle), irradiated, split, and subjected to CuAAC with either light-(turquoise rectangle) or heavy-labeled (purple rectangle) isoDTB azide.…”
mentioning
confidence: 99%